2019
DOI: 10.3390/w11101990
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Drivers of Water Consumption in Single-Family Households in Joinville, Southern Brazil

Abstract: This study aims to identify the factors that may influence water consumption in single-family households in the city of Joinville, Southern Brazil. Through questionnaires, data were collected from 108 households in several neighborhoods of the city. The questionnaires contained open-ended and closed-ended questions involving the surrounding infrastructure, socio-economic and demographic characteristics, constructive characteristics, installed plumbing fixtures, and water-use habits, totaling 57 variables. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
11
0
3
Order By: Relevance
“…De acuerdo con diferentes autores, el consumo de agua en los hogares depende de variables tales como el clima (temperatura, precipitaciones, humedad atmosférica), factores económicos y sociales (habitantes por vivienda, estrato social, nivel de educación, ingresos familiares, precio del agua), factores culturales (sistema de valores, conciencia ambiental de los ciudadanos, modelos sociales) y por el uso de dispositivos hidráulicos ahorradores (p. ej. aireadores de grifo o inodoros de bajo consumo) y/o la reutilización de aguas grises domésticas (Manco et al, 2012;Marinoski et al, 2018;García et al, 2019;Khalid et al, 2019). El análisis de estas variables, en un contexto particular, es fundamental para la planificación hídrica, debido a que permite evaluar medidas de gestión para fomentar la conservación del agua y reducir su uso inadecuado en viviendas residenciales (García et al, 2019).…”
unclassified
See 1 more Smart Citation
“…De acuerdo con diferentes autores, el consumo de agua en los hogares depende de variables tales como el clima (temperatura, precipitaciones, humedad atmosférica), factores económicos y sociales (habitantes por vivienda, estrato social, nivel de educación, ingresos familiares, precio del agua), factores culturales (sistema de valores, conciencia ambiental de los ciudadanos, modelos sociales) y por el uso de dispositivos hidráulicos ahorradores (p. ej. aireadores de grifo o inodoros de bajo consumo) y/o la reutilización de aguas grises domésticas (Manco et al, 2012;Marinoski et al, 2018;García et al, 2019;Khalid et al, 2019). El análisis de estas variables, en un contexto particular, es fundamental para la planificación hídrica, debido a que permite evaluar medidas de gestión para fomentar la conservación del agua y reducir su uso inadecuado en viviendas residenciales (García et al, 2019).…”
unclassified
“…aireadores de grifo o inodoros de bajo consumo) y/o la reutilización de aguas grises domésticas (Manco et al, 2012;Marinoski et al, 2018;García et al, 2019;Khalid et al, 2019). El análisis de estas variables, en un contexto particular, es fundamental para la planificación hídrica, debido a que permite evaluar medidas de gestión para fomentar la conservación del agua y reducir su uso inadecuado en viviendas residenciales (García et al, 2019).…”
unclassified
“…Considering residential buildings, Garcia et al [20] identified drivers for water consumption in 108 single-family households using questionnaires. Variables investigated include socioeconomic and demographic characteristics, construction data, water appliances and water-use habits.…”
Section: Definition Of Variables and Clustering Analysismentioning
confidence: 99%
“…In order to provide a better understanding of the impact of reservoirs in the availability of water in South America, we examined the relationship between water availability and the estimated water consumption (WC) in the continent. Despite the fact that many authors have studied water consumption on the continent [82][83][84][85][86][87], the majority of the research conducted to date is focused on local areas within the different countries of the continent. Furthermore, estimates of water consumption vary greatly for each country in South America due to the region's great climatic diversity, different social customs, and different levels of economic income.…”
Section: Estimates Of Water Consumption and Potential Water Availability In South Americamentioning
confidence: 99%